Modeling the parameters of hot radioactivity release as a result of an accident at Chernobyl nuclear power plant. (November 2020) - Mehdi, M; Panin, M P; Pripachkin, D A; Mohemmedi, B
Abstract: A three-dimensional Computational Fluid Dynamics (CFD) model is used to simulate the dispersion of radioactive gas from the Chernobyl accident. The most important features of the model are a totally 3-dimensional advection–diffusion equation. Computing the rise of the plume from an accident is an important point for estimating the release of radioactive gas into the atmosphere. The analysis of the plume rise at the time of the Chernobyl accident presents some special circumstances. This is caused by the very high temperature resulting from the burning of graphite. The modeling was performed using Reynolds-Averaged Navier-Stokes RANS method using the k-ε model delivered by the commercial code ANSYS-Fluent. The results of the simulation were verified against the measurements taken by aircraft.